(untitled) (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Fibroadenomas are common benign breast tumors, particularly in young women, while giant fibroadenomas, defined as those exceeding 5 cm, are rare. TP53 mutations are generally associated with malignancies and are seldom observed in benign breast lesions. The Arg72Pro polymorphism of TP53 is a low-penetrance variant that may modulate cancer susceptibility. Aim & Objectives: This report presents a rare case of a giant fibroadenoma harboring a TP53 codon 72 Pro/Pro polymorphism and explores its potential relevance in early cancer risk stratification. Material & Methods: A 19-year-old female presented with a palpable breast lump. Surgical excision was performed, and histopathology confirmed a giant fibroadenoma. Immunohistochemistry for p53 protein was carried out to assess protein expression. Genomic DNA from peripheral blood was analyzed for TP53 mutations, focusing on codon 72 polymorphism. A literature review was conducted to contextualize TP53 variants in benign breast disease. Results: The excised tumor measured 7.5 cm and displayed benign histology without atypia or malignancy. p53 immunohistochemistry was negative, indicating no protein accumulation. Genetic analysis revealed a homozygous Pro/Pro genotype at codon 72, with no pathogenic high-penetrance TP53 mutations detected. Previous studies suggest that this variant may modestly increase cancer susceptibility in specific populations. Conclusion: This case demonstrates a rare coexistence of a TP53 Pro/Pro polymorphism in a benign giant fibroadenoma. While the lesion itself was benign, the presence of a low-penetrance TP53 variant may provide insight into subtle cancer predisposition. These findings underscore the potential role of such polymorphisms as early biomarkers for risk assessment and highlight the need for further research into their prognostic and preventive implications.